Pelatihan Desain Canva dan Google Drive Dalam Pengelolaan Strategi Promosi - Mutmainah; Andik Susanto (Universitas Merdeka Madiun, 2024)
One thing that attracts people to make purchases is product photos. Producing excellent and attractive product photos requires extra effort in designing and editing them. An application is needed that can help entrepreneurs, especially